A Combined Biophysical and Economic GIS Framework to Assess Sugarcane Cropping Potential in Brazil. Issue 3 (June 2014) - Hissa, Letícia de Barros Viana; Filho, Britaldo Silveira Soares
Abstract Recently, the increasing demand for biofuels triggered a new phase for the sugar‐alcohol sector. In Brazil, as well as in other tropical countries, this process raised worries regarding the possible direct and indirect effects of the crop's expansion on the conversion of native vegetation coverings. Therefore, the modeling of spatial‐economic surfaces, representing the potential rent variation in its spatial component, for economic activities, may be a useful tool in the decision‐making process. Hence, here we propose and present the results of a combined framework composed of two modules using the modeling platform Dinamica EGO. The first module simulates sugarcane's growth, calculating the daily response of the crop to environmental conditions during the stages of the plant's development. The second module estimates rents for sugarcane cultivation in Brazil, identifying areas where this activity would bring higher economic return, looking at simulated productivity, production costs and selling prices in a way that is spatially explicit for Brazil. Two different scenarios for production costs were tested, and results ranged from negative values to maxima of R/ha 929 and R/ha 1176 for standard and efficient costs of production, respectively. The model successfully indicated non‐profitable and profitable areas, and regions where high expected economic return overlaps endangered ecosystems.